The genome of the forest insect pest Pissodes strobi reveals genome expansion and evidence of a Wolbachia endosymbiont. Issue 4 (16th February 2022) - Gagalova, Kristina K; Whitehill, Justin G A; Culibrk, Luka; Lin, Diana; Lévesque-Tremblay, Véronique; Keeling, Christopher I; Coombe, Lauren; Yuen, Macaire M S; Birol, Inanç; Bohlmann, Jörg; Jones, Steven J M
Abstract: The highly diverse insect family of true weevils, Curculionidae, includes many agricultural and forest pests. Pissodes strobi, commonly known as the spruce weevil or white pine weevil, is a major pest of spruce and pine forests in North America. Pissodes strobi larvae feed on the apical shoots of young trees, causing stunted growth and can destroy regenerating spruce or pine forests. Here, we describe the nuclear and mitochondrial Pissodes strobi genomes and their annotations, as well as the genome of an apparent Wolbachia endosymbiont. We report a substantial expansion of the weevil nuclear genome, relative to other Curculionidae species, possibly driven by an abundance of class II DNA transposons. The endosymbiont observed belongs to a group (supergroup A) of Wolbachia species that generally form parasitic relationships with their arthropod host.